Dairy producers in the Southeast United States are concerned with cow care and welfare. Issue 1 (5th February 2020) - Lee, Amanda; Schexnayder, Susan; Schneider, Liesel; Oliver, Stephen; Pighetti, Gina; Petersson-Wolfe, Christina; Bewley, Jeffrey; Ward, Stephanie; Krawczel, Peter
Abstract: This research communication addresses the hypothesis that Southeast dairy producers' self-reported bulk tank somatic cell count (BTSCC) was associated with producers' response to three statements (1) 'a troublesome thing about mastitis is the worries it causes me, ' (2) 'a troublesome thing about mastitis is that cows suffer, ' and (3) 'my broad goals include taking good care of my cows and heifers.' Surveys were mailed to producers in Georgia, Kentucky, Mississippi, North Carolina, South Carolina, Tennessee, and Virginia (29% response rate, N = 596; final analysis N = 574), as part of a larger survey to assess Southeastern dairy producers' opinions related to BTSCC. Surveys contained 34 binomial ( n = 9), Likert scale ( n = 7), and descriptive ( n = 18) statements targeted at producer self-assessment of herd records, management practices, and BTSCC. Statements 1 and 2 were assessed on a 5-point Likert scale from 'strongly disagree' to 'strongly agree.' Statement 3 was assessed on a 5-point Likert scale from 'very unimportant' to 'very important.' Reported mean BTSCC for all participants was 254 500 cells/ml. Separate univariable logistic regressions using generalized linear mixed models (SAS 9.4, Cary, NC, USA) with a random effect of farm, were performed to determine if BTSCC was associated with probability for a producer's response to statements. If BTSCC was significant, forward manual addition was performed until no additional variables were significant ( P ≤ 0.05), but included BTSCC, regardless of significance. Bulk tank somatic cell count was associated with 'a troublesome thing about mastitis is the worries it causes me, ' but not with Statements 2 or 3. This demonstrates that >75% of Southeastern dairy producers are concerned with animal care and cow suffering, regardless of BTSCC. Understanding Southeast producers' emphasis on cow care is necessary to create targeted management tools for herds with elevated BTSCC.